Papers - Ground Movement and Subsidence - Subsidence Resulting from the Athens System of Mining at Negaunee, Michigan (With Discussion) - Charles W. Allen (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
The Athens mine is in the city of Negaunee, Mich. It is one of the larger producers of soft hematite ore on the Marquette iron range. The property is held under lease by the Athens Iron Mining Co., and is operated by the Cleveland-Cliffs Iron Co., which is a partner with Pickands, Mather & Co. in the Athens company. The mine was opened in 1913, and shipments of ore commenced in 1918, the total reaching 3,063,711 tons up to Jan. 1, 1932. Diamond-drilling from surface, together with a knowledge of geological conditions in neighboring properties, gave a comprehensive picture of the location, size and shape of the orebody before shaft-sinking started. Striking east and west, the orebody entered the east boundary of the property at a depth of about 1500 ft. below surface. A pitch of 15" to the west carried it down to about 2500 ft. on the west boundary, about double the depth of that of any soft-ore property heretofore worked on the Marquette Range. The width of ore averaged close to 500 ft., and the thickness 300 feet. The depth of the deposit and its size, together with an overburden of quicksand, which in places reached a thickness of 150 ft., presented unusual mining problems. The use of a caving system made surface drainage into the orebody inevitable, because the north boundary of the deposit was a vertical diorite dike 200 ft. wide, and the south boundary a northward-dipping impervious slate. S. R. Elliott, manager of the mining department of the Cleveland-Cliffs Iron Co., who was superintendent of the mine at that time, conceived the idea of starting at the bottom of the orebody and working upward, reversing the usual mining procedure. This innovation divided the Athens orebody into a series of steps, or blocks, the first of which was adjacent to the western boundary, and therefore in the lowest portion of the deposit. Top-slicing was to start under the capping in this first block by raising from the bottom level, and development and mining were to progress upward in successive blocks to the east. A complete description of the Athens system of mining was